Pengaruh Citra Merek, Persepsi Harga, Dan Kualitas Layanan Terhadap Keputusan Pembelian Internet First Media di Kota Surabaya - Pratama, Julian (Seminar Nasional Ilmu Terapan, 2024)
The digital era is increasingly developing until now with the presence of very sophisticated technology to improve internet providers, including in the field of goods and services. This research aims to analyze and test the influence of brand image, price perception and service quality on First Media internet purchasing decisions in Surabaya. This research uses quantitative methods with data collection techniques through questionnaires distributed to 100 First Media internet user respondents in Surabaya. The population in this study was the population of Gading Village, totaling 28,350 residents. Meanwhile, the sample is 100 residents of Gading Village, who already use First Media WiFi internet. The research variables consist of independent variables: brand image (X_1), price perception (X_2), service quality (X_3), and dependent variable: purchasing decision (Y). The data analysis technique uses multiple linear regression analysis techniques. The research results show that brand image, price perception and service quality have a significant influence on purchasing decisions in the Gading sub-district in Surabaya. This proves that the higher the brand image, price perception and quality of service provided, the higher the consumer's purchasing decisions.